2021
DOI: 10.2215/cjn.06740521
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Pediatric Kidney Transplantation under the New Kidney Allocation System in the United States

Abstract: Background and objectivesIn December 2014, the Kidney Allocation System (KAS) was implemented to improve equity in access to transplantation, but preliminary studies in children show mixed results. Thus, we aimed to assess how the 2014 KAS policy change affected racial and ethnic disparities in pediatric kidney transplantation access and related outcomes.Design, setting, participants, & measurementsWe performed a retrospective cohort study of children <18 years of age active on the kidney transplant lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Black children continued to have the lowest transplant rates of all racial/ethnic groups. Conversely, Shelton et al reported an increase in transplant rate among Black pediatric candidates in the first 2 years after the introduction of KAS, 8 and Krissberg et al reported no change in waiting time 17 . Among adult candidates, Melanson et al reported an increase in transplant rate among Black and Hispanic adult candidates, but this increase was attenuated in more recent data 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Black children continued to have the lowest transplant rates of all racial/ethnic groups. Conversely, Shelton et al reported an increase in transplant rate among Black pediatric candidates in the first 2 years after the introduction of KAS, 8 and Krissberg et al reported no change in waiting time 17 . Among adult candidates, Melanson et al reported an increase in transplant rate among Black and Hispanic adult candidates, but this increase was attenuated in more recent data 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Racial disparities were another key target of KAS, although they were not as significant in pediatric candidates pre‐KAS; Krissberg et al report a time ratio for the time from activation to transplant among Black candidates that were 1.14 (95% CI 1.00–1.29) relative to Caucasian candidates 17 . However, our data did not show any increase in the transplant rate among Black and Hispanic candidates, even though transplant rates for Caucasian candidates increased significantly.…”
Section: Discussionmentioning
confidence: 99%
“…The 2014 Kidney Allocation System (KAS) deprioritized HLA matching and has narrowed the disparity in waitlist time among Black and Hispanic candidates and improved their transplant rates (72,73). Unfortunately, the same policy had the unintended consequence of prolonging pediatric waitlist times, highlighting the need for critical appraisal that policy change can have on clinical outcomes (74)(75)(76). Because organ allocation is an entangled dynamic system, in which change to one factor can significantly impact the others, prioritization of only one element often fails and highlights the pressing need to develop an allocation model that can optimize immunological matching but that can preserve pediatric priority, as well as minimize racial and geographic disparities (77,78).…”
Section: Methodsmentioning
confidence: 99%
“…Pediatric KT candidates and their families face increasingly complex choices under the kidney allocation system (KAS). [1][2][3] KAS policies aimed to improve longevity matching between donors and recipients and increase access for underserved populations. 4 While KAS successfully reduced deceased donor kidney transplant (DDKT) disparities between Black and White adult recipients (and some pediatric recipients), the overall rate of pediatric KT decreased.…”
Section: Introductionmentioning
confidence: 99%